Reputation, honesty, and cheating in informal milk markets in India - Markus Kröll; Devesh Rustagi (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
Sellers display astounding differences in their cheating behavior, even in developing countries with weak enforcement of rules. Using the context of informal milk markets in India, we examine the role of reputation and norms of honesty as potential explanations. Our results show that individuals cannot verify milk quality, which weakens the scope of reputation-based mechanisms. But a strong correlation exists between milk quality and norms of honesty, measured using a novel behavioral experiment. Price collusion allows for the coexistence of honest and dishonest milkmen within a market. Norms of honesty can mitigate market inefficiency under the right institutional environment.
Keywords: C93; D00; O13; Q01; 330; Cheating; informal sector; reputation; norms of honesty; milk markets; India